Fundamental Locomotor Skill Proficiency in Phase a Primary Students: An Observational Study of Walking, Running, and Jumping - Kaban, Ika Oktarina br; Siregar, Samsudi; Octavia , Syalwa; Nasution, Diyah Salsabil; Mutia, Mutia; Tamba, Kuntum; Dalimunthe, Arif Rahman; Pebriansyah, Wahyu; Banjarnahor, Ramelina (Journal of Foundational Learning and Child Development, 2026)
Purpose of the study: Fundamental locomotor skills—walking, running, and jumping—constitute the motor foundation upon which more complex physical competencies are developed during early childhood and primary school years. Adequate mastery of these skills is essential not only for physical performance but also for cognitive engagement, social participation, and lifelong physical activity habits. This study aimed to describe and assess the fundamental locomotor movement abilities of Phase A first-grade elementary school students, specifically examining walking, running, and jumping proficiency during Physical Education (PE) learning activities at SD Ibnu Halim, Medan, Indonesia. Materials and methods: A qualitative descriptive research design was employed. Twelve students (6 males, 6 females; mean age 6.5 ± 0.5 years) were purposively selected as participants. Data were collected across three structured observation sessions using a validated locomotor skill observation rubric, supplemented by semi-structured teacher interviews and document analysis. Data were analyzed through thematic analysis comprising data reduction, data display, and conclusion drawing. Lincoln and Guba’s trustworthiness criteria (credibility, transferability, dependability, and confirmability) were applied to ensure rigor. Results: Walking demonstrated the highest proficiency rate (75.0%), characterized by consistent rhythmic gait and adequate dynamic balance. Running showed moderate proficiency (58.3%), with over 40% of participants displaying postural compensation and inconsistent arm–leg coordination. Jumping exhibited the lowest proficiency (33.3%), with the majority of students unable to execute proper two-foot takeoff mechanics and controlled landing techniques. Thematic analysis revealed four overarching themes influencing locomotor development: movement experience, pedagogical strategy, individual variation, and feedback quality. Conclusions: Phase A first-grade students demonstrate locomotor abilities consistent with normative developmental expectations; however, significant refinement is required, particularly in jumping skills. Physical Education instruction should adopt game-based, exploratory, and differentiated approaches to optimize locomotor competency development. Teachers must provide structured guidance, timely corrective feedback, and sufficient practice opportunities aligned with each child’s developmental stage.